Interpretation of Yield and Yield Components in Some Barley (Hordeum vulgare L.) Genotypes with Different Analysis Techniques - Karaman, Mehmet (Institute of Economic Development and Social Researches, 2023)
Barley, with its high protein and β-glucan content, is important in animal nutrition, in the malt industry as a quality malt source, and sometimes by finding in different proportions in human food. In the study, it was determined that there were significant differences at p<0.01 level between genotypes in all traits and two different main clusters were formed. According to the heatmap based on morphological association; in the first main cluster; number of grains per spike (GN), spike weight (SW) and spike yield (SY) were place take. In the second main cluster; spike length (SL), grain yield (GY) and number of spike per square meter (SN) were find. In addition, in terms of the examined features; It can be said that the advanced stage lines G2 and G6 were the most similar, while G1 and G3 were the most different. Six-row barley genotypes were found to be superior to two-row genotypes in all traits examined, except for the SN and SL. When all analysis methods were evaluated together, it was determined that the SN was highly correlated (r= 0.5544**) with GY. In the study; it has been determined that the G7 and G9 advanced stage lines were superior to all control varieties in terms of GY. However, it would be useful to repeat the study for at least one more year in order to make a definitive interpretation. © 2023, Institute of Economic Development and Social Researches. All rights reserved.
Bazı Arpa (Hordeum vulgare L.) Genotiplerinde Verim ve Verim Komponentlerinin Farklı Analiz Teknikleri ile Yorumlanması
Keywords: Barley; Correlation; Gge Biplot; Grain Yield; Heatmap